Happiness in marriage - Sanger, Margaret, 1879-1966 (Pergamon, 1969)
Happiness in Marriage is a book written by a prominent birth control activist, women's rights advocate, sex educator, and nurse Margaret Sanger in response to the letters she received from women seeking aid in marriage problems. The book, intending to solve the different and usual problems found in marriage, discusses the first step and building life forces; the different stages - courtship, engagement, honeymoon, and settling down; sex-related questions and issues, including psychic impotence and frigidity; the avoidance of premature parenthood; and birth control in practice. The text is reco.